The effect of the electric field and neutral winds on E-region ion densities and conductivities at low latitudes - Slnghal R.P. (My University, 2025)
A model to calculate electron densities and electrical conductivities in the ionospheric E-region at low latitudes has been developed. Calculations have been performed under photochemical equilibrium and including plasma transport due to the electric field and neutral winds. Results have been compared with observations at Arecibo (18.15°N, 66.20°W), Thumba (8°32′N, 76°51′E) and SHAR (14.0°N, 80.0° E). Good agreement is obtained for Arecibo. For Thumba and SHAR agreement is satisfactory for altitudes above 110 km. Below 100 km, model predictions are too low in comparison with the observed data. The effect of plasma transport on electron densities and Hall and Pedersen conductivities is investigated in detail. A combination of neutral winds and a downward (or westward) electric field can compress the plasma into a thin layer. An upward electric field along with the neutral winds gives rise to a broad, multilayered profile. The ratio of height-integrated Hall to Pedersen conductivities changes from 1.2 to 2 in some cases. © 1991.